Surgical Menopause and Bilateral Oophorectomy: Effect of Estrogen-Progesterone and Testosterone Replacement Therapy on Psychological Well-Being and Sexual Functioning; A Systematic Literature Review - Stuursma, Annechien; Lanjouw, Lieke; Idema, Demy L; de Bock, Geertruida H; Mourits, Marian J E (Oxford University Press, 2022)
Background: Besides experiencing vasomotor symptoms, after surgical menopause and bilateral salpingo-oophorectomy (BSO), women experience moderate to severe psychological and sexual symptoms. Aims: To systematically review and meta-analyze the effect of systemic hormone replacement therapy (sHRT) on psychological well-being and sexual functioning in women after surgical menopause and BSO. Methods: Medline/Pubmed, EMBASE and PsychInfo were systematically searched until November 2021. Randomized controlled trials investigating the effect of sHRT on psychological well-being and/or sexual functioning in surgically menopausal women and women after BSO were eligible for inclusion. Two independent authors performed study selection, risk of bias assessment and data extraction. Standardized mean differences (SMDs) were calculated. Outcomes: Primary outcomes for psychological well-being were defined as overall psychological well-being, depression, and anxiety. Primary outcomes for sexual functioning were defined as overall sexual functioning, sexual desire, and sexual satisfaction. All outcomes were assessed on short (≤12 weeks) or medium term (13–26 weeks). Results: Twelve studies were included. Estradiol had a beneficial effect on depressed mood on short term 3–6 years after surgery or 2 years (median) after surgery with high heterogeneity (SMD: −1.37, 95%CI: −2.38 to −0.37, P = .007, I 2 79%). Testosterone had a beneficial effect on overall sexual functioning on short to medium term 4.6 years (mean) after surgery (SMD 0.38, 95%CI 0.11–0.65, I 2 0%) and on sexual desire on medium term at least 3–12 months after surgery (SMD 0.38, 95%CI 0.19–0.56, I 2 54%). For most studies, risk of bias was uncertain. Clinical implications: Estradiol may beneficially affect psychological symptoms after surgical menopause or BSO and testosterone might improve sexual desire and overall sexual functioning. Strengths and limitations: This review only included patient-reported outcomes, thereby reflected perceived and not simply objective symptoms in surgically menopausal women and women after BSO. The small number of studies highly varied in nature and bias could not be excluded, therefore our results should be interpreted with great caution. Conclusion: Independent randomized controlled clinical trials investigating the effects of estrogen-progesterone and testosterone on psychological and sexual symptoms after surgical menopause are needed. PROSPERO registration number: CRD42019136698. Stuursma A, Lanjouw L, Idema DL, et al. Surgical Menopause and Bilateral Oophorectomy: Effect of Estrogen-Progesterone and Testosterone Replacement Therapy on Psychological Well-being and Sexual Functioning: A Systematic Literature Review. J Sex Med 2022;19:1778–1789.
Keywords: BRCA1/2 mutation; Hormone replacement therapy; Oophorectomy; Psychosexual functioning; Testosterone; General Medicine